PREVENTING TERRORIST ATTACKS AT SEA maritime terrorism risk and international law. - Bowley, Robin ([S.l.] : ROUTLEDGE, 2022)
Over recent decades, it has been widely recognised that terrorist attacks at sea could result in major casualties and cause significant disruptions to the free flow of international shipping. After discussing the overlaps and distinctions between piracy and maritime terrorism, this book considers how the International Ship and Port Facility Security Code, and other vessel identification and tracking measures in the 1974 International Convention for the Safety of Life at Sea, would be likely to reduce the risk of terrorist attacks at sea. It explains how the 1982 United Nations Convention on the Law of the Sea is less than clear on the powers of states to protect offshore installations, submarine cables and pipelines from interference by terrorists. In light of these uncertainties, it considers how the 2005 Protocol to the Convention for the Suppression of Unlawful Acts Against Maritime Navigation, the doctrine of necessity and states' inherent self-defence rights might apply in the maritime security context. A significant contribution of the book is the formulation of the Maritime Terrorism Threat Matrix, which provides a structured framework for examining how maritime terrorism incidents have occurred, and might occur in the future. The book also examines the relevant national maritime security legislation for preventing maritime terrorist attacks in the United Kingdom and in Australia. The book concludes by formulating guidelines for the unilateral interdiction of suspected terrorist vessels in exceptional circumstances, and recommending priorities for governments and international maritime industries to focus on in order to reduce the risk for terrorist attacks at sea. It will be of interest to those working in the areas of Law and Terrorism, Law of the Sea, Maritime Law and Insurance and International Law.
OCLC-licensed vendor bibliographic record.
Keywords: Maritime terrorism -- Law and legislation; Terrorism -- Prevention -- Law and legislation; LAW / Maritime; LAW / International; LAW / Public